Distance Creativity Education with Digital Technology in the Art and Culture Subject of Gloria 2 Christian Senior High School Surabaya - Hasprita Restiamangastuti Boru Mangunsong (JPP (Jurnal Pendidikan dan Pembelajaran), 2022)
Arts and Culture as an art subject in high school serves as a balancer in the midst of most lessons that prioritize rationality. The COVID-19 pandemic and technological developments encourage distance learning to take place by relying on digital technology. The purpose of this article is to describe a distance learning strategy for Cultural Arts with digital technology at Gloria 2 Christian Senior High School Surabaya to increase creativity. The method used is qualitative by observing learning styles, learning behavior, interests, student needs, facilities owned by students which are then used to design distance learning. The strategies used include planning, implementation and evaluation, all of which use digital technology. Student learning outcomes are quite satisfactory by showing the development of creative abilities in making works as well as appreciation and multidimensional abilities in carrying out appreciation activities